2019
DOI: 10.1016/j.chempr.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Quenching Mechanism of Light-Harvesting Complexes of Plants by Zooming in on the Ensemble

Abstract: The light-harvesting complexes (LHCs) of plants can regulate the energy flux to the reaction centers in response to fluctuating light by virtue of their vast conformational landscape. They do so by switching from a light-harvesting state to a quenched state, dissipating the excess absorbed energy as heat. However, isolated LHCs are prevalently in their light-harvesting state, which makes the identification of their photoprotective mechanism extremely challenging. Here, ensemble time-resolved fluorescence exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 61 publications
12
78
3
Order By: Relevance
“…The Chl a have the lowest energy levels, which are the emissive states that give rise to each component. The existence of three components indicates multiple Chl a emissive sites within LHCSR3, consistent with previous models of LHCs (Mascoli et al 2019, Mascoli et al 2020, Krüger et al 2010, Krüger et al 2011. The two dynamic components arise from changes in the extent of quenching of the Chl emitters.…”
Section: Roles Of Ph and Zea In Fluorescence Intensity In Vivo And Insupporting
confidence: 88%
“…The Chl a have the lowest energy levels, which are the emissive states that give rise to each component. The existence of three components indicates multiple Chl a emissive sites within LHCSR3, consistent with previous models of LHCs (Mascoli et al 2019, Mascoli et al 2020, Krüger et al 2010, Krüger et al 2011. The two dynamic components arise from changes in the extent of quenching of the Chl emitters.…”
Section: Roles Of Ph and Zea In Fluorescence Intensity In Vivo And Insupporting
confidence: 88%
“…The biexponential decay kinetics of Chl a L imply two subpopulations with different levels of quenching, likely reflecting a quenched conformation and an unquenched one 58,59 . Recent transient absorption studies on CP29, a minor antenna complex homologous to LHCII, found a similar biexponential decay of the terminal Chl a excited state, which was attributed to the coexistence of quenched and unquenched conformations 60 . The coexistence of multiple conformations with distinct photophysics is further supported by single-molecule fluorescence measurements that identified unquenched and quenched conformations of LHCII 61,62 and other homologous complexes 63,64 .…”
Section: Resultsmentioning
confidence: 87%
“…This switch can be experimentally evidenced though measurements of change in the excited-state lifetime of the complex. For monomeric CP29, lifetimes changing from ∼100 ps to about 4 ns have been recently observed [56], and associated to quenched and lightharvesting states, respectively.…”
Section: Resultsmentioning
confidence: 96%